Analisis Alih Kode Dalam Novel “Dear Allah” Karya Diana Febi - Devina Damayanti; Ita Kurnia; Nerina Tita Rahmadani (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This research examines the form of code switching and code mixing in the novel "Dear Allah" by Diana Feby. The aim is to describe the form of code switching in the novel. The results showed that there was code switching in the form of: a) Indonesian to Arabic switching and b) Indonesian to English switching c) Indonesian to Javanese switching. There are factors that cause code-switching in the novel "Dear Allah" by Diana Febi which is due to the presence of speakers or speakers, interlocutors or listeners, changes in the topic of conversation and the subject matter.